Anti‐ictogenic and antiepileptogenic properties of brivaracetam in mature and immature rats. (25th March 2015) - Dupuis, Nina; Matagne, Alain; Staelens, Ludovicus; Dournaud, Pascal; Desnous, Béatrice; Gressens, Pierre; Auvin, Stéphane
Summary Objective Brivaracetam (BRV) is a new antiepileptic drug candidate rationally designed for high affinity and selectivity for the synaptic vesicle protein 2A. This study explored anti‐ictogenic and antiepileptogenic effects of BRV in rats at different stages of development. Methods Using a rapid kindling model in P14, P21, P28, and P60 rats, we studied two doses of BRV: 10 and 100 mg/kg injected intraperitoneally 30 min before afterdischarge assessment. We also assessed blood and brain concentrations of BRV 30 min after the injection. Results BRV 100 mg/kg significantly increased the afterdischarge threshold (ADT) at all ages, whereas BRV at 10 mg/kg increased ADT in P60, P28, and P21 rats. BRV also shortens the afterdischarge duration (ADD), achieving statistical significance with 10 and 100 mg/kg at P60 and with 100 mg/kg at P21. At P60, BRV increases the number of stimulations required to achieve a stage 4–5 seizure in a dose‐dependent manner. At P28 and P21, BRV increased the number of stimulations required to develop a stage 4–5 seizure in a dose‐dependent manner with almost complete elimination of stage 4–5 seizures. In contrast, at P14, BRV had no effect on the number of stage 4–5 seizures. An age‐related decrease in blood and brain concentrations of BRV was observed 30 min after injection of BRV 10 mg/kg, whereas with 100 mg/kg there were no significant age‐correlated differences in brain and serum BRV concentrations. Significance BRV exerted dose‐dependent anti‐ictogenic effects from P60 to P14 independent of brain maturation. BRV also exhibited antiepileptogenic effects at P60, whereas this effect need to be further evaluated at P28 and P21. We did not observe any effect on epileptogenesis at P14 at either dose.